2015
DOI: 10.1016/j.cis.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative review of the transition salt concentration for inhibiting bubble coalescence

Abstract: Some salts have been proven to inhibit bubble coalescence above a certain concentration called the transition concentration. The transition concentration of salts has been investigated and determined by using different techniques. Different mechanisms have also been proposed to explain the stabilising effect of salts on bubble coalescence. However, as yet there is no consensus on a mechanism which can explain the stabilizing effect of all inhibiting salts. This paper critically reviews the experimental techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 89 publications
6
70
1
1
Order By: Relevance
“…This concept is further elaborated in Section 3.4. Generally, these results suggest that the stabilization of the homogeneous flow regime and, thus, the changes in the gas holdup are caused by the modifications to the BSDs and are induced by the coalescence suppression/enhancement mechanisms (connected to the bubble interface properties, (Firouzi et al, 2015;Lucas, 2009, 2010)), as previously observed by the authors for an aqueous solution of ethanol . The detailed relationship between the bubble interface properties and the BSDs are a matter for ongoing and future studies.…”
Section: Image Analysis -"Bubble-scale"supporting
confidence: 64%
See 1 more Smart Citation
“…This concept is further elaborated in Section 3.4. Generally, these results suggest that the stabilization of the homogeneous flow regime and, thus, the changes in the gas holdup are caused by the modifications to the BSDs and are induced by the coalescence suppression/enhancement mechanisms (connected to the bubble interface properties, (Firouzi et al, 2015;Lucas, 2009, 2010)), as previously observed by the authors for an aqueous solution of ethanol . The detailed relationship between the bubble interface properties and the BSDs are a matter for ongoing and future studies.…”
Section: Image Analysis -"Bubble-scale"supporting
confidence: 64%
“…This is interesting because the d eq -φ space is determined by the properties at the bubble interface (the reader may refer, for example, to ref. (Firouzi et al, 2015): despite the fact that the topic is different, the framework is similar, as previously discussed). This result, taking into account that the "dual effect of viscosity over BSDs", supports the hypothesis that the stabilization of the homogeneous flow regime is caused by the large number of small "non- G. Besagni et al Chemical Engineering Science 158 (2017) 509-538 coalescence-induced bubbles".…”
Section: Image Analysis -"Bubble-scale"supporting
confidence: 50%
“…Indeed, it is known that most electrolytes inhibit bubble coalescence in pure liquid phases [63][64][65][66][67][68] and, as a consequence, the homogeneous flow regime is stabilized [69,70]. For example, owing to their influence, the prevailing flow regime may change from heterogeneous to homogeneous, due to surfactant addition [71] as the boundary between the flow regimes changes.…”
Section: Influence Of the Liquid Phase Viscositymentioning
confidence: 99%
“…Influence of the Active Compounds: Inorganic Compounds ("positive surfactants") Inorganic compounds (i.e., electrolyte solutions) are attracted to the interface where they adsorb positively, lower the surface tension, cause coalescence suppression and, finally, stabilize the homogeneous flow regime [63][64][65][66][67][68]. Indeed, it is known that most electrolytes inhibit bubble coalescence in pure liquid phases [63][64][65][66][67][68] and, as a consequence, the homogeneous flow regime is stabilized [69,70].…”
Section: Influence Of the Liquid Phase Viscositymentioning
confidence: 99%
“…気泡流には様々なスケールがあり、気泡が生成 する乱れは多くの研究者の注目を集めている。そ の乱れは、流れ場と相互作用し、単相流とは異な る複雑な流動構造を示す [1][2][3][4][5][6]。特に気泡クラスタ ーは、乱流の秩序渦構造よりも大きく、大規模な 流動構造そのものを変化させる [7,8]。 そのため気 泡クラスター形成の有無について様々な報告が 行われている [9][10][11]。 気泡のクラスター形成は、まず理論的に予測さ れた。ポテンシャル流れを仮定し、複数の気泡が 上昇する際、気泡間相互作用によって水平面に気 泡 が クラスターを 形成することが報告された [12,13]。一方で、実際の気泡流では、気泡同士の 合体によって気泡径差が生まれ、通常気泡のクラ スター構造は観察されない。さらに前述のポテン シャル流れを用いた理論でも、気泡径差を考慮す るとクラスターは形成されない [14]。しかし、実 験的研究において、界面活性剤や電解質を混入さ せることで気泡クラスターの形成が報告されて いる [15,16]。 界面活性剤や電解質の混入は、気泡表面の境界 条件を大きく変化させる。界面活性剤では気泡の 抗力の増加や合体を防ぎ、電解質ではやクリーン な気泡を保ちながら気泡合体を防ぐ [17][18][19][20] /01 02 0/%/ü ! 1 ö 3 4 5 6 7 8 9 6 % !ú ÷ ù ' ü ü ö !…”
Section: 緒 言unclassified